Corneal Stromal Abscess in a Dog - Marinho, Karoline Alves de Oliveira; Tavernezi, Karen Medina Teixeira; Alves, Breno Henrique; Souza, Bruna Carioca de; Silva, Carolina Ferreira; Pereira, Gabriele Flaviane; Carvalho, Lígia Maria de; Júnior, Sávio Tadeu Almeida (Acta Scientiae Veterinariae, 2022)
ABSTRACT Background: The eye is an important sense organ responsible for sight. The cornea is the outermost of many eye layers, being predisposed to several lesions, some of them being frequent in small animal clinics meanwhile others are unusual and seldom reported in specialized literature. The stroma abscess is a common condition in horses, but atypical in dogs, it's a condition in which a microperforation in the corneal epithelium allows microorganisms or a foreign body to penetrate the corneal stroma, and those become inside the cornea after a re-epithelialization, producing an intense inflammatory response. Therefore, this case reports a case of deep stromal abscess in a Shih Tzu dog. Case: A 4-year-old female Shih Tzu, weighing 4.6 kg, was submitted to ophthalmic examination in which the left eye presented an opaque yellowish-white protruding structure located on the right side, in the center of the cornea (3 o´clock position), bulbar and palpebral conjunctival hyperemia and congestion, chemosis, blepharospasm, and a moderate amount of mucous discharge. The clinical diagnosis was stromal abscess with reflex uveitis. A differential diagnosis should include conditions affecting the anterior part of the cornea, such as an epithelial inclusion cyst and a corneal ulcer. The inclusion cyst, contrarily to the corneal abscess, doesn't cause pain, meanwhile, the corneal ulcer was ruled out by the Fluorescein Staining Test. The recommended treatment was surgical, through lamellar keratectomy, followed by overlapping pedicled conjunctival graft and third eyelid flap. In association with the surgical treatment, oral antibiotics, anti-inflammatory, and opioids, plus topical antibiotics and autologous serum eye drop. Seventy days post-surgery, the previously observed inflammatory signs were no longer present. In the conjunctival graft insertion site perpetuated a scar leucoma with few blood vessels. The therapy was proven effective in solving the stromal abscess and in visual maintenance. Despite the located opacity due to leucoma, it barely causes any impairment, once its lateral position won't impact the central vision, which is more important to predator species than the peripheral vision. Discussion: Stromal abscess is a pathological condition in which an initial perforating corneal injury leads to a rupture of the epithelial barrier, allowing the access of bacterial, fungus, or foreign bodies of organic nature. The morbidity is more frequent in horses, but this report shows that although uncommon, stromal abscesses can occur in dogs. The diagnosis was achieved by an analysis of the clinical history and findings. Conditions that affect the anterior cornea must be among differential diagnoses. Treatment aims for the removal of infectious material with debridement and curetting of the stroma, by performing the lamellar keratoplasty technique, which produces a corneal wound. The implementation of a pedicled conjunctival graft allows, the influx of growth factors, active replication of stromal collagen by fibroblasts, and direct arrival of antibiotics through the blood supply to the exposed portion of the cornea. The third eyelid flap is questioned by some authors, once it complicates the post-op follow up, and hinder the topical therapy from directly reaching the eye surface. Autologous serum: A blood-derived product often used to control corneal melting. The Federal Medicine Board determined that autologous serum eyedrops therapy has been scientifically proven effective, being used worldwide in the treatment of severe eye surface conditions. In Veterinary, studies also demonstrated that autologous serum can improve improve the corneal re-epithelialization in dogs. Keywords: autologous serum, keratectomy, ophthalmology, veterinary. Título: Abscesso estromal em córnea de cão Descritores: soro autólogo, ceratectomia, oftalmologia, veterinária.